Public Perception of Courier Fare Issue Management and Shopee Express Expedition - Anggaraksa Adwitiya Arrazy; Juan Malik Frederick Turpyn (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2021)
Technological developments are growing rapidly, with the result that create phenomenon marketplace. Indonesia, which is still following the development of marketplaces or e-commerce also continues to encourage the utilization of equal opportunities for sellers on the platform including Shopee. As in some time ago, Shopee Indonesia was hit by the issue of oppression of Shopee Express couriers as well as the slow expedition of goods throughout the country due to the impact of both problems. Responding to concerns about courier fares and Shopee Express expeditions, based on the results of issue life cycle that Shopee Indonesia immediately took a strategy and quick response steps in order to manage the issue as soon as possible. The research method that will be used is qualitative descriptive with data collection techniques used are observation, interviews, and document analysis. The result of this research is, it can be concluded public perception of courier fare issue management and shopee express expedition raises various negative and positive aspects of varied public perceptions. What happens to Shopee Indonesia can happen with anyone. Keep in mind that the purpose of PR activities is to shape the reputation of the organization and then maintain it. Therefore, Shopee Indonesia must remain consistent in maintaining its reputation so that similar problems do not occur in the future.